Wild river : a novel - Philbrick, W. R. (W. Rodman) (Scholastic Inc., 2022)
When a dam fails and rushing waters sweep away their adult supervisors, five middle schoolers on a white-water rafting adventure are left alone with few supplies and the opportunity to forge powerful bonds as well as develop dangerous disagreements.